2015
DOI: 10.1371/journal.pone.0126936
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Infection and Fertility Alteration: A Systematic Review

Abstract: BackgroundHPV is the most prevalent sexually transmitted infection and its effect in cancer induction is well documented. HPV infections are mostly asymptomatic, but it is unclear whether HPV infections can result in alterations of reproductive health.ObjectiveTo determine the relationship between human papillomavirus infections and reproductive health in both men and women.MethodsA systematic literature review was performed in PubMed and ScienceDirect data bases from January 1994 through August 2014.ResultsHP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
82
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 37 publications
(43 reference statements)
1
82
0
11
Order By: Relevance
“…Sexually transmitted infections such as Chlamydia trachomatis , Neisseria gonorrhoeae, and HPV may affect fertility or reproductive outcomes [36, 37]. Our meta-analysis results showed that there was no significant association between HPV infection and pregnancy rate of ART, with a pooled RR of 1.04 (95% CI 0.64–1.70).…”
Section: Discussionmentioning
confidence: 82%
“…Sexually transmitted infections such as Chlamydia trachomatis , Neisseria gonorrhoeae, and HPV may affect fertility or reproductive outcomes [36, 37]. Our meta-analysis results showed that there was no significant association between HPV infection and pregnancy rate of ART, with a pooled RR of 1.04 (95% CI 0.64–1.70).…”
Section: Discussionmentioning
confidence: 82%
“…Dichos datos demuestran que la prevalencia detectada puede estar relacionada con la inmunosupresión relativa observada en mujeres embarazadas 22 . Sin embargo, la infertilidad humana deriva de múltiples factores que son los responsables de las disfunciones reproductivas en hombres y/o mujeres, tales como los trastornos congénitos y hormonales, el estilo de vida, los riesgos medioambientales y el estado psicológico que afecta a la función de los órganos genitales, la producción de células reproductivas, la calidad del semen, el transporte de los espermatozoides a los oocitos, la fertilización y los procedimientos de implantación embrionaria 23 .…”
Section: Discussionunclassified
“…Los factores bacterianos bien establecidos e identificados que pueden originar alteraciones de la fertilidad incluyen: Neisseria gonorrhoeae, Treponema pallidum y Chlamydia trachomatis, aunque existen otras infecciones no reconocidas (virus del herpes humano, virus adenoasociados, VIH, citomegalovirus humano y VPH) como factores asociados a la alteración de la reproducción 23 . Hong et al reportaron una menor adhesión de los embriones de ratón expuestos al VPH-16 en comparación con los controles 24 ; además, diversos autores han reportado ADN del VPH en las placentas de abortos espontáneos 5,[24][25][26][27] .…”
Section: Discussionunclassified
“…It is unclear whether HPV infections can silently affect the reproductive function as it appears that HPV can be associated with apoptosis of sperm and embryonic cells and alterations in semen quality. 5 Giant condyloma presents clinically as an exuberant exophytic growth of a condyloma acuminatum that typically appears after an infection with the low-risk HPV types 6 or 11 with the anus, penis, perineum, vulva, and to a lesser extent the cervix being the most common affected sites.…”
Section: Discussionmentioning
confidence: 99%